Checklist of the Decapods (Crustacea) from the outer continental shelf and seamounts from Northeast of Brazil— REVIZEE Program (NE III) - Filho, Petrônio A.c. (Zootaxa, 2006)
This study presents a list of 142 species collected on the outer continental shelf and seamounts from northeast Brazil at 24 oceanographic stations in May, 1998. References are provided from which all the present taxa identifications are based on.